The Influence of Leverage, Investment Opportunity Set on Accounting Conservatism: The Moderating Effect of Political Connections - Yunina Yunina; Erra Sahfira; Mursidah Mursidah; Naz'aina Naz'aina; Indrayani Indrayani (Department of Accounting, Faculty of Economics & Business, 2026)
This study investigates the influence of leverage and investment opportunity set on accounting conservatism, with political connections serving as a moderating variable. The sample comprises 125 non-financial companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023, yielding 375 firm-year observations, selected through purposive sampling based on specific criteria. This quantitative research employs panel data collected through documentation techniques from the official IDX website (www.idx.co.id) and the respective companies’ official websites. The data were analyzed using Moderated Regression Analysis (MRA) in EViews 12. The findings reveal that leverage has no significant effect on accounting conservatism, whereas the investment opportunity set has a negative and significant effect. Additionally, political connections do not moderate the relationship between leverage and accounting conservatism but do moderate the relationship between the investment opportunity set and accounting conservatism.